Effects on growth performance and immunity of Monopterus albus after high temperature stress - Mao, Yifan; Lv, Weiwei; Huang, Weiwei; Yuan, Quan; Yang, Hang; Zhou, Wenzong; Li, Mingyou (Frontiers in Physiology, 2024)
To investigate the impact of the effect of high temperature stimulation on Monopterus albus larvae after a certain period of time, five experimental groups were established at different temperatures. Then, the M. albus under high temperature stress was fed at 30 ℃ for 70 days. After that, the growth index of the M. albus was counted and analyzed. High temperature stress had significant effects on growth indicators of M. albus (P<0.05). The SR increased after being stimulated by temperature (P<0.1).The study revealed that liver cells of M. albus were harmed by elevated temperatures of 36℃ and 38℃. In the experimental group, the activities of digestive enzymes changed in the same trend, reaching the highest point in the 32℃ group and then decreasing, and the AMS activity in the 38℃ group was significantly different from that in the 30℃ group (P<0.05). The activities of antioxidase in liver reached the highest at 34℃, which was significantly different from those at 30℃ (P<0.05). The expression levels of TLR1, C3, TNF-α, and other genes increased in the experimental group, reaching the highest point at 34℃, and the expression level of the IL-1β gene reached the highest point at 32℃, which was significantly different from that at 30℃ (P<0.05). However, the expression level of the IRAK3 gene decreased in the experimental group and reached its lowest point at 34℃ (P<0.05). The expression level of the HSP90α gene increased with the highest temperature stimulus (P<0.05). In the α diversity index of intestinal microorganisms in the experimental group, the observed species, Shannon, and Chao1 indexes in the 34℃ group were the highest (P<0.05), and β diversity analysis revealed that the intestinal microbial community in the experimental group was separated after high temperature stimulation. At the phylum level, the three dominant flora are Proteus, Firmicutes, and Bacteroides. Bacteroides and Macrococcus abundance increased at the genus level, but Vibrio and Aeromonas abundance decreased. To sum up, appropriate high-temperature stress can enhance the immunity and adaptability of M. albus. These results show that the high temperature stimulation of 32-34 ℃ is beneficial to the industrial culture of M. albus.